2020
DOI: 10.1093/ajcp/aqaa194
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolar Adenoma/Pulmonary Ciliated Muconodular Papillary Tumor

Abstract: Objectives To describe the histologic features that are helpful in the diagnosis of the rare bronchiolar adenomas/ciliated muconodular papillary tumors (BAs/CMPTs) during intraoperative consultation. Methods Multi-institutional retrospective review of frozen sections of 18 BAs/CMPTs. Results In 14 of 18 cases, BA/CMPT was the primary reason for sublobar lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…In particular, for proximal-type BA/ CMPT, with prominent mucinous features and peripheral skip lesions, the differential diagnosis includes IMA. The challenge of distinguishing CMPT/BA from adenocarcinoma, especially IMA, during intraoperative consultation has been highlighted in several studies, 176,185,186 because the presence of cilia and basal cells may be subtle in frozen sections.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In particular, for proximal-type BA/ CMPT, with prominent mucinous features and peripheral skip lesions, the differential diagnosis includes IMA. The challenge of distinguishing CMPT/BA from adenocarcinoma, especially IMA, during intraoperative consultation has been highlighted in several studies, 176,185,186 because the presence of cilia and basal cells may be subtle in frozen sections.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…A total of 134 BA/CMPT lesions were found in the literature from 2010 to 2021; 53 BAs in nine reports (nine lesions were excluded because of duplicates, and 13 lesions that did not meet the definition of BA wereexcluded, 3,[28][29][30][33][34][35][36][37] and 81 CMPTs in 26 reports (11 lesions were excluded because of duplicates). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23][24][25][26][27]31,32 Of these, 94 (70.1%) were interpreted as proximal-type BA, and 25 (18.6%) were interpreted as distal-type BA, whereas 15 lesions (11.1%) could not be categorized as either of them.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Bronchiolar adenomas grow slowly and are usually detected when they are small. To date, no recurrence has been reported, 3–37 and its excellent prognosis suggests that BA is a benign tumor. The majority of BAs have driver mutations including BRAF V600E, unusual EGFR exon 19 deletions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is challenging to distinguish CMPT from mucinous adenocarcinomas in frozen slides because of the abundant mucous lakes and the difficulty in recognizing ciliated columnar cells in the small floating cells. 6,7 However, CMPT does not represent nuclear atypia or mitotic activity, as against mucinous adenocarcinoma. 8,9 A distinctive molecular feature of the tumor is a single driver mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, the tumor has been misdiagnosed as a mucinous adenocarcinoma on intraoperative frozen section analysis. Shirsat et al reported that only 16.7% of cases were diagnosed as CMPT during intraoperative frozen studies 6 . It is challenging to distinguish CMPT from mucinous adenocarcinomas in frozen slides because of the abundant mucous lakes and the difficulty in recognizing ciliated columnar cells in the small floating cells 6,7 .…”
Section: Discussionmentioning
confidence: 99%